Multi-temporal shoreline analysis and future regional perspective for Kuwait coast using remote sensing and GIS techniques - Ikram M.S. Al-Attar; Manar A. Basheer (Heliyon, 2023)
Coastal regions are of extraordinary significance for the financial and welfare of human communities. Unfortunately, coastal regions are naturally pressured by anthropogenic activities that increase their vulnerability. Hence, there is a drastic need to monitor coastal changes to protect and manage them sustainably. Since Kuwait's coast is inhabited by about 94% of the inhabitants and most of the metropolitan area and the urgent need for sustainable planning and management of Kuwait's coast, this paper aims to analyze the historical changes rate of Kuwait's coast and Kuwait islands over 40 years from 1980 to 2020 and to predict the future changes of the shoreline in 2035 using EPR model. The results show that the highest accretion rate of the shoreline is 32.79 m/year, while the lowest erosion rate is −23.45 m/year. EPR of the islands revealed a fluctuation between erosion and deposition at each island. The future predicted shoreline changes were also mapped for the shoreline and islands.